Early prophylactic antibiotics administration for acute necrotizing pancreatitis: a meta‐analysis of randomized controlled trials. (9th February 2015) - Ukai, Tomohiko; Shikata, Satoru; Inoue, Machiko; Noguchi, Yoshinori; Igarashi, Hisato; Isaji, Shuji; Mayumi, Toshihiko; Yoshida, Masahiro; Takemura, Yousuke C.
Abstract: Background: The effectiveness of prophylactic antibiotics use for acute necrotizing pancreatitis has been explored and a number of systematic reviews have been published with conflicting results. The timing of antibiotics administration can be fundamental to their effectiveness, but thus far no reviews have focused on the timing of administration. Methods: A systematic review of randomized controlled trials (RCTs) of prophylactic antibiotics for acute necrotizing pancreatitis was conducted using MEDLINE (PubMed), CINAHL and Japana Centra Revuo Medicina. Trials in which antibiotics were administered within 72 h after onset of symptoms or 48 h after admission were included. Our primary outcomes were the mortality rate and the incidence of infected pancreatic necrosis, and secondary outcomes were the incidence of non‐pancreatic infection and the incidence of surgical intervention. Results: The search revealed six RCTs with a total of 397 patients. The mortality rates were significantly different for those taking antibiotics (7.4%), and controls (14.4%) (odds ratio [OR], 0.48; 95% confidence interval [CI], 0.25–0.94). Also, early prophylactic antibiotics use was associated with reduced incidence of infected pancreatic necrosis (antibiotics 16.3%, controls 25.1%; OR, 0.55; 95% CI, 0.33–0.92). Conclusion: Early use of prophylactic antibiotics for acute necrotizing pancreatitis is associated with reduced mortality and lower incidence of infected pancreatic necrosis.